Fabrication Of Lead Sulfide (Pbs) Nanostructures For Solar Cell Applications - Al-Qayssie, Ahmed Salman Obaid (2013)
The main aim of the research work presented in this thesis was to synthesise nanostructured PbS absorber layer for solar cell devices using simple and economical methods: chemical bath deposition (CBD), microwave assisted chemical bath deposition (MACBD) and thermal evaporation (TE). The synthesis of nanostructured PbS layers using CBD was carried out by changing Pb2+ ions source, deposition time, and molar concentration. The results showed that the morphology and size-scale of nanostructured PbS features are highly dependent on each parameter. X-ray diffraction analysis (XRD) analysis revealed that all nanostructured PbS thin films exhibit a cubic rock salt (NaCl) type structure. The optimal condition to synthesise nanostructured PbS using CBD was lead nitrate as Pb2+ ions source with 0.1M molar concentration. The PbS sample with optimum conditions was selected to be used as an absorber layer on the PbS/CdS/ITO solar cell device.